Semantic and Syntaxic Analysis of the 2024 Presidential Debate: A Case Study of Van Dijk's Approach - Salvia Micca; Ririn Rahayu; Masithah Mahsa (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to analyze the semantics and syntax of Teun A. van Dijk's model in the third presidential debate of the 2024 presidential candidates. This study uses a descriptive qualitative approach. The data in this study are oral discourses in the 2024 presidential debate uploaded by the Indonesian General Elections Commission (KPU RI) YouTube channel with the theme of security, defense, globalization, international relations, geopolitics, and foreign policy. The data source in this study was obtained from the KPU RI YouTube channel with the title "Third Debate of Presidential Candidates for the 2024 Election" which was held on January 7, 2024. The data collection techniques used were documentation techniques, listening techniques, and note-taking techniques. Based on the results of the study, it was found that syntactic elements were more dominant than semantic ones. The most prominent syntactic element was the use of active sentences used by the presidential candidates to build a firm and convincing self-image to the public. Meanwhile, semantic elements were found through background, details, intentions, presuppositions, and nominalizations that shape local meanings in the discourse. It can be concluded that the presidential debate is not just a forum for a contest of ideas, but also a space for the struggle for meaning through structured linguistic strategies. These findings demonstrate how political language is constructed to influence public opinion and shape perceptions of power in a democratic space. Thus, Van Dijk's approach reveals the relationship between language and power in the context of modern political debate.